Stability Constants of Lanthanide(III) Chelates of 8-Quinolinol-5-Sulfonate - Turkel, Naciye (Asian Journal of Chemistry, 2010)
The stability constants of complexes of 8-quinolinol-5-sulfonate with scandium(lll), yttrium(III) and lanthanum(III) were determined potentiometrically in 0.1 M sodium chloride solution at 25°C. Along with the ordinary first complexes, second and third complexes (ML+, ML2, ML33+ were also observed in solutions of 8-quinolinol-5-sulfonate that contains metal ions. The stoichiometries of formed complexes were defined by Job's method. The results showed that the values of the stability constants of the first, second and third complexes increase [Sc(III) > Y(III) > La(III)] with decreasing metal ionic radius.